2012
DOI: 10.1002/ptr.4722
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Aldose Reductase Inhibitory Activity of Standardized Extracts and the Major Constituent of Andrographis paniculata

Abstract: Aldose reductase is the first enzyme in the polyol pathway and catalyzes the reduction of glucose to sorbitol by coupling with the oxidation of NADPH to NADP(+) . This sorbitol accumulation leads to various diabetic complications, including neuropathy, nephropathy, cataracts, and retinopathy. In the present study, aldose reductase inhibitory (ARI) activity of the methanolic as well as standardized extracts of Andrographis paniculata (Burm. f.) Wall. ex Nees (Acanthaceae) and its chief constituent, andrographol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In a study, the methanol extract of A. paniculata and AGL were found to decrease galactitol accumulation in rat lens ( in vitro ) and galactosemic rat model ( in vivo ) ( Veeresham et al, 2013 ). Zhou et al (2013) also introduced two important AGL derivatives (compounds 1 and 7, Figure 1 ) having antidiabetic activity.…”
Section: Resultsmentioning
confidence: 99%
“…In a study, the methanol extract of A. paniculata and AGL were found to decrease galactitol accumulation in rat lens ( in vitro ) and galactosemic rat model ( in vivo ) ( Veeresham et al, 2013 ). Zhou et al (2013) also introduced two important AGL derivatives (compounds 1 and 7, Figure 1 ) having antidiabetic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperglycemia due to diabetes causes the activation of aldose reductase that leads to sorbitol [39][40][41][42][43] and fructose production. These two products can induce oxidative stress leading to alteration in normal physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Veeresham et al ., reported that the methanolic and standardized extracts of Andrographis paniculata (Burm. f.) Wall.…”
Section: Introductionmentioning
confidence: 99%